PEMBERIAN HAK PELAYANAN KESEHATAN BAGI NARAPIDANA DALAM KEADAAN OVERCROWDED DI LEMBAGA PEMASYARAKATAN - Ruth Mirel Amabel; Mitro Subroto (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
Overcrowded penitentiary housing has an impact on the health conditions of inmates. the occupancy rate of prisoners which tends to increase every year is not proportional to the number of Correctional Institutions. The problem of this research is how to grant the right to health services to convicts and what obstacles are faced in granting the right to health services to overcrowded convicts in correctional institutions. This research is a descriptive study with a qualitative approach using primary and secondary data sources. This research shows that granting the right to health services for convicts who are overcrowded in Correctional Institutions is an effort to improve the health status of prisoners through health services and environmental health service efforts by increasing human resources for health services, health service facilities, health service financing, availability of drugs and equipment. -medical devices. Obstacles faced in granting the right to health services to prisoners in a state of overcrowding in Correctional Institutions include limited Human Resources for Health Service Officers, Health Service facilities, Health Service Financing, availability of Medicines and Medical Devices and low awareness of prisoners in carrying out efforts to maintain health.